Macrofocal multiple myeloma in young patients: A distinct entity with favorable prognosis - Dimopoulos, M.A.; Pouli, A.; Anagnostopoulos, A.; Repoussis, P.; Symeonidis, A.; Terpos, E.; Delimbasi, S.; Tsolakis, F.; Economopoulos, T.; Zervas, C. (Leukemia and Lymphoma, 2006)
There are limited reports of young patients with multiple myeloma (MM) who presented with multiple lytic bone lesions but without intervening infiltration of bone marrow, a pattern consisting of macrofocal MM. In order to clearly define the clinical and laboratory features and outcome of such patients, a retrospective analysis was performed of symptomatic patients with MM ≤40 years of age at diagnosis who received primary treatment over a 20-year period. Ten of 51 patients fulfilled the criteria of macrofocal MM. When compared to patients with typical MM, patients with macrofocal pattern were less anemic, none had hypercalcemia, renal impairment, elevated serum LDH or stage 3 according to the International Staging System (ISS). Patients with macrofocal MM usually had preserved the uninvolved immunoglobulins. An objective response to primary treatment was noted in 55% of patients with macrofocal MM and in 50% of patients without this pattern. The median survival of patients with typical MM was 57 months and is projected to exceed 8 years in patients with macrofocal MM (p = 0.087). With macrofocal MM despite multiple lytic bone lesions, patients have features of low tumor burden and improved survival when compared with young patients with typical MM.
Keywords: Macrofocal; myeloma; Prognosis; Young age